Preservation of wood works using fungicides against biological deterioration - Abdul Halim, Nurul Adida; Barkeshli, Mandana (2012)
Wood is subject to deterioration from a number of biological agents including insects, marine borer, bacteria and fungi. Fungi can cause more deterioration in wood than any agent does. In conservation treatment, a fungicide is used to prevent such biological deterioration in wooden artifact. The synthetic fungicides such as Boric acid, Arsenic compound, Zinc chloride and Tributyltin oxide are chemical compounds usually applied in wood preservation. Some of them were removed from a market due to their harmful effect on human health and residue problem. The aim of this paper is to review the advantages and disadvantages of a current treatment used in wood preservation by using organic and inorganic fungicides. Among the advantages is the efficiency of the product to stop and to prevent a growth of the fungus. Meanwhile, the disadvantages are toxicity material and heavy metal poisoning. Liquid preservation use as a fungus treatment could be done in several ways, including the use of natural based fungicide. It is recommended that from the review, a further study on the possibility of using plant extraction as a fungicide could be conducted using a mince garlic and vinegar.